Extreme Hydroclimate Events Between Early‐1100s and Mid‐1200s Recorded in Deep Springs Lake, California - Jianru Cheng; Huifang Xu (Geophysical Research Letters)
Abstract Previous studies reported megadroughts in southwestern North America during the Medieval Climate Anomaly and subsequent periods. However, previous local records challenge traditional tree‐ring based indices. Through mineralogical analyses of Deep Springs Lake sediments in California, we examined carbonate mineral assemblages as novel hydroclimate proxies. Our investigation revealed a primary magnesite‐rich layer (∼70% Ca‐bearing magnesite, ∼30% dolomite) beneath a layer dominated by aragonite and calcite, implying a transition from an extreme drought to pluvial conditions. Since magnesite precipitates only at the highest Mg:Ca ratios, followed by dolomite and calcite/aragonite, we developed the quantitative Carbonate Dryness Index (CDI) by weighting these minerals. The CDI curve highlights a drought and a following pluvial with unparalleled magnitudes in the past millennium during 1090–1150 CE, aligning with nearby local climate proxies but not regional tree‐ring records. Additionally, DSL sediments recorded ∼500‐year wet/dry cycles driven by solar and El Niño‐Southern Oscillation (ENSO) activities.